Nitric oxide and cardiovascular disease. Issue 864 (October 1997) - McIntyre, M.; Dominiczak, A. F.
Abstract : Endothelium-derived nitric oxide is an important regulatory molecule in cardiovascular function. Reduced availability of nitric oxide has been implicated in the pathogenesis of hypertension and atherosclerosis.